(untitled) (mathematica didactica, 2002)
The notion of averaging in its numerous variations has been a central theme in all areas of mathematics from its very beginnings in Babylon 4000 years ago to Pythagoreans and the present time. A basic idea in the descriptive sense, it has also proved, in the normative sense, to be useful in teaching mathematics.